Internet das Coisas no Cen??rio Rural assistida por Arquitetura H??brida Sat??lite - terrestre 5G - Costa , Karine de Lourdes Mateus da (2021)
Satellite components are unquestionably essential to address the challenges relating to support of ubiquitous coverage, global IoT (Internet of Things), machine-to-machine communications, telecommunications mission-critical, and an increase in multimedia traffic. New paradigms of hybrid satellite-terrestrial architecture have therefore been explored, mainly in WRAN (Wireless Regional Area Network) and eRAC (enhanced Remote Area Communications) scenarios. The aim is to extend the provision of services to remote areas in a variety of sectors, such as smart environments and transport, agriculture, aeronautics, military, and maritime, among others. Therefore, this work integrates, configures, investigates, and evaluates the performance of a remote IoT application operating from a 5G hybrid network, thus contributing to the advancement of agribusiness in continental ountries. For this purpose, an intelligent system was developed to monitor and control the irrigation of a vegetable garden in a rural area. The use of the hybrid network to provide adequate connectivity for WRAN, eRAC, and IoT applications was confirmed through a scenario that connected the cities of Santa Rita do Sapuca??-MG and Hortol??ndia-SP. Tests in the IoT context presented acceptable results, with round-trip delays between the extreme points of the test scenario ranging from 500 ms to 1600 ms. The test environment consists of a hybrid satellite-terrestrial network architecture implemented using the integration of the SES14 satellite and a pair of 5G GFDM (Generalized Frequency Division Multiplexing) modems with a rural IoT application, both developed and implemented for this work.